Development of a 0D multi-zone model for fast and accurate prediction of homogeneous charge compression ignition (HCCI) engine - Fasulo Giovanni (EDP Sciences, 2021)
Homogeneous Charge Compression Ignition (HCCI) is a promising advanced combustion mode, featured by both high thermal efficiency and low emissions. In this context, a 0D multi-zone model has been developed, where the thermal stratification in the combustion chamber has been taken into account. The model is based on a control mass Lagrangian multi-zone approach. In addition, a procedure based on a tabulated approach (Tabulated Kinetic of Ignition - TKI) has been developed, to perform an accurate and fast prediction of the air/fuel mixture auto-ignition. This methodology allows combining the accuracy of detailed chemistry with a negligible computational effort. The tabulated procedure has been preliminarily verified through the comparison with the results of a commercial software (GT-Power™). In this assessment, single zone simulations have been performed comparing the TKI strategy to a conventional chemical kinetics one, in four different cases at varying the intake temperature and the equivalence ratio. Then, the proposed 0D multi-zone model has been validated against experimental data available in the literature. The analyses are carried out with reference to an HCCI engine fuelled with pure hydrogen and working in a single operating point, namely 1500 rpm, 2.2 bar IMEP and with a fuel/air equivalence ratio of 0.24. Three different temperatures, i.e., 373, 383, and 393 K, have been considered for the intake air. The experimental/numerical comparisons of pressure cycles and burn rates proved that the proposed numerical approach can reproduce the experiments with good accuracy, without the need for case-by-case tuning.